Children as robot designers - Alves-Oliveira, P. (2021)
We present the design process of the robot YOLO aimed at stimulating creativity in children. This robot was developed under a human-centered design approach with participatory design practices during two years and involving 142 children as active contributors at all design stages. The main contribution of this work is the development of methods and tools for child-centered robot design. We adapted existing participatory design practices used with adults to ft children’s development stages.We followed the Double-Diamond Design Process Model and rested the design process of the robot on the following principles: Low foor and wide walls, creativity provocations, open-ended playfulness, and disappointment avoidance through abstraction. The fnal product is a social robot designed for and with children. Our results show that YOLO increases their creativity during play, demonstrating a successful robot design project.We identifed several guidelines that made the design process successful: the use of toys as tools, playgrounds as spaces, the emphasis of playfulness for child expression, and child policies as allies for design studies. The design process described empowers children’s in the design of robots.